An index-based holistic approach to evaluate flood preparedness: evidence from Bangladesh - Rahman, Md. Mostafizur; Islam, Md. Rakibul; Shobuj, Ifta Alam; Hossain, Md. Tanvir; Ahsan, Md. Nasif; Alam, Edris; Al Hattawi, Khawla Saeed; Islam, Md. Kamrul (Frontiers in Climate, 2024)
IntroductionThis study aims to assess individual flood preparedness in the flood-prone Islampur Union of Sunamganj District, Bangladesh, using an index-based Holistic Individual Preparedness Model (HIPM).MethodsA total of 510 respondents participated in a face-to-face field survey, which employed 21 flood preparedness indicators. The key objectives were to evaluate the extent of individual preparedness and its determinants. Statistical methods such as multiple linear regression and Spearman’s rank correlation were used to analyze the relationship between preparedness and various sociodemographic factors.Results and discussionThe results show that 91% of respondents felt insecure during floods and 86% experienced damage to their homes. A significant proportion (87%) rated flood warnings as inadequate, while 84% did not seek refuge in flood shelters. Notably, 54% of respondents demonstrated limited knowledge of flood preparedness measures. Factors like gender, housing type, monthly income, and evaluation of flood warnings were associated with preparedness levels, with females and residents of kacha (unsafe) houses being less prepared. The study underscores the need for targeted campaigns and educational initiatives to improve preparedness, particularly for vulnerable groups.